Reaktualisasi Amanat Agung dalam Era Digital: Strategi Pertumbuhan Gereja di Tengah Disrupsi Teknologi - Sembodo, A. Srihadi Bambang; Timadius, Hendrik; Y.P, Remegises Danial (Peneliti.net, 2026)
This study addresses the gap between the theological understanding of the Great Commission and its practical implementation in church ministry within the digital era. At the same time, technological disruption has introduced significant challenges, including the weakening of faith communities and the fragmentation of teaching authority, thereby underscoring the urgency of reactualizing the Great Commission as a holistic and contextual strategy for church growth. The aim of this study is to explore how the church can integrate theological reflection on the Great Commission with ministry practices in the digital sphere, as well as to formulate contextual ministry strategies that support sustainable church growth. This research employs a literature review methodology. The findings reveal that church growth in the era of technological disruption can be effectively realized through the transformation of digital ministry that is coherently grounded in the theological principles of the Great Commission.